An Updated Classification System and Review of the Lipooligosaccharide Biosynthesis Gene Locus in Campylobacter jejuni - Hameed, Amber; Woodacre, Alexandra; Machado, Lee R.; Marsden, Gemma L. (Frontiers in Microbiology, 2020)
Lipooligosaccharide is an integral component of the Campylobacter cell membrane with a structure of core oligosaccharides forming inner and outer core regions and a lipid A moiety. The gene content of the lipooligosaccharide core biosynthesis cluster exhibits extensive sequence variation which leads to the production of variable cell surface lipooligosaccharide structures in Campylobacter. Some lipooligosaccharide outer core molecules in Campylobacter jejuni are molecular mimics of host structures (such as neuronal gangliosides) and are thought to trigger neuronal disorders (particularly Guillain-Barré Syndrome and Miller Fisher Syndrome) in humans. The extensive genetic variation in the LOS biosynthesis gene cluster, a majority of which occurs in the lipooligosaccharide outer core biosynthesis gene content present between lgtF and waaV, has led to the development of a classification system with 23 classes (A-W) and four groups (1-4) for the Campylobacter jejuni lipooligosaccharide region. This review presents an updated and simplified classification system for LOS typing alongside an overview of the frequency of Campylobacter jejuni lipooligosaccharide biosynthesis genotypes and structures in various Campylobacter jejuni populations.